Production of Antiviral Substance from Sugarcane Bagasse by Chemical Alteration of its Native Lignin Structure through Microwave Solvolysis. Issue 17 (12th May 2020) - Kimura, Chihiro; Li, Ruibo; Ouda, Ryota; Nishimura, Hiroshi; Fujita, Takashi; Watanabe, Takashi
Abstract: The production of bioactive agents from lignocelluloses has received limited attention because plant cell walls are essentially non‐bioactive. In this study, a chemical reaction is reported, which produces a lignin‐derived antiviral substance from sugarcane bagasse by microwave heating at 200 °C in aqueous glycerol containing 0.5 % H2 SO4 . The purified fraction, designated as FR200, strongly inhibited the replication of encephalomyocarditis virus (EMCV) in L929 cells without cytotoxicity. HSQC NMR spectra demonstrated that the principal interunit linkages in the native lignin were cleaved by the reaction. Gel permeation chromatography (GPC) and pyrolysis‐GCMS revealed that FR200 is composed of oligomeric lignin with a weight average molecular weight of approximately 2000. When the bagasse was reacted at lower temperatures, 140 °C and 160 °C, the native lignin substructures were partially retained and the antiviral activity significantly decreased. The results thus indicate that the antiviral activity emerged through severe alteration of the native lignin structure. Furthermore, it was revealed that the antiviral lignin inactivated the EMCV virions through direct contact, as the innate immune system of L929 was not activated by FR200 treatment, and no antiviral activity was found when L929 was pre‐treated with the lignin before viral infection. Abstract : Plant cells fighting viruses : The production of bioactive agents from lignocelluloses has received limited attention because plant cell walls are essentially non‐bioactive. In this study, a chemical reaction is reported, which produces a lignin‐derived antiviral substance from sugarcane bagasse by microwave heating at 200 °C in aqueous glycerol containing 0.5 % H2 SO4 . The purified fraction strongly inhibited the replication of encephalomyocarditis virus in L929 cells without cytotoxicity.